Peranan Mahasiswa dan Alumni dalam Mempertahankan Akreditasi A pada Prodi Hukum Ekonomi Syariah (Muamalah) Fakultas Syariah dan Hukum UINSU Medan - Tetty Marlina Tarigan; Fatimah Zahara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article discusses the role of students and alumni in maintaining accreditation. This study uses a qualitative method with a historical approach. The role of students and alumni is very much needed in advancing and also maintaining the accreditation of the department. One of the forums that need to be fostered and developed its roles and functions and supported by its existence by the universities, especially in each study program, is the existence of associations in the form of alumni associations. Through professional alumni organization, various kinds of opportunities and opportunities will be well communicated.